2002
DOI: 10.1046/j.1460-9568.2002.02073.x
|View full text |Cite
|
Sign up to set email alerts
|

Early sequential formation of functional GABAA and glutamatergic synapses on CA1 interneurons of the rat foetal hippocampus

Abstract: During postnatal development of CA1 pyramidal neurons, GABAergic synapses are excitatory and established prior to glutamatergic synapses. As interneurons are generated before pyramidal cells, we have tested the hypothesis that the GABAergic interneuronal network is operative before glutamate pyramidal neurons and provides the initial patterns of activity. We patch-clamp recorded interneurons in foetal (69 neurons) and neonatal P0 (162 neurons) hippocampal slices and performed a morphofunctional analysis of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 49 publications
7
101
0
1
Order By: Relevance
“…The present results further strengthen this point, showing that, before day 6, monosynaptic MF-CA3 responses are mainly GABAergic because DNQX-sensitive glutamatergic currents could be seen only after increasing stimulus strength two or more times. This finding is consistent with the sequential expression of functional GABA and glutamatergic synapses found in the hippocampus at early developmental stages (6,27).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present results further strengthen this point, showing that, before day 6, monosynaptic MF-CA3 responses are mainly GABAergic because DNQX-sensitive glutamatergic currents could be seen only after increasing stimulus strength two or more times. This finding is consistent with the sequential expression of functional GABA and glutamatergic synapses found in the hippocampus at early developmental stages (6,27).…”
Section: Discussionsupporting
confidence: 89%
“…1A). It should be stressed that, in the immediate postnatal period, GABAergic interneurons innervating mainly the apical dendrites of pyramidal neurons are located in stratum radiatum, whereas collateral from other CA3 pyramidal neurons are still poorly developed (27). GABAergic inputs (from interneurons) were identified on the basis of their insensitivity to and their ability to be blocked by picrotoxin.…”
Section: Methodsmentioning
confidence: 99%
“…Tyzio et al (1999) showed that spiking CA1 pyramidal neurons in the neonatal hippocampus can be either silent, show GABAergic PSCs, or show both GABA and glu inputs, strongly suggesting the silent neuron 3 GABA 3 glu sequence of excitability and afferent connectivity. The same sequence was observed in CA1 pyramidal neurons of the embryonic macaque (Khazipov et al, 2001) and in CA1 GABAergic interneurons of embryonic rats (Hennou et al, 2002). In contrast, the order of appearance of fast and slow GABAergic afferents in the developing hippocampus has not been clearly established.…”
Section: Similarities Between the Developing And Adult Hippocampusmentioning
confidence: 51%
“…In addition, it needs to migrate, mature, and establish presynaptic and postsynaptic connections. In the developing hippocampus, this process has been studied extensively (Lübbers and Frotscher, 1988;Laurie et al, 1992;Super and Soriano, 1994;Tyzio et al, 1999;Hennou et al, 2002;Gozlan and Ben Ari, 2003;Jones et al, 2003), but the sequence of events leading to neuronal maturation in the adult hippocampus remains unknown. Given the differences in the developing and adult environments, the process of maturation and the factors that modulate it may also differ.…”
Section: Introductionmentioning
confidence: 99%
“…The trophic effects of GABA on neuronal migration and neurite growth during the embryonic and perinatal period are largely explained by its depolarizing action in immature neurons, which triggers calcium influx and signaling [23,24,25]. In fact, GABA signaling in the neonatal brain represents an early form of neural communication, which precedes and promotes the formation of glutamatergic synapses [26][27][28]. GABA signals are transduced through two general classes of receptors, the metabotropic GABA B receptors and ionotropic GABA A Rs which are permeable to chloride ions.…”
Section: Introductionmentioning
confidence: 99%